Viral Gastroenteritis Outbreaks in Deployed British Troops During 2002-7. Issue 3 (1st September 2008) - Bailey, Mark S; Gallimore, CI; Lines, LD; Green, AD; Lopman, BA; Gray, JJ; Brown, DWG
Abstract : Objectives: The aim of this study was to see what lessons could be learnt from the suspected viral gastroenteritis outbreaks that have occurred in deployed British troops during 2002-7. Method: Epidemiological and laboratory data from identifiable outbreaks were reviewed, including epidemic curves and the results of PCR testing for enteropathic viruses. Results: The epidemic curves of outbreaks varied predictably in accordance with the size of the population at risk and whether this population was constant or expanding. Of 11 outbreaks identified, 10 (91%) had a proven viral cause and 10 (91%) occurred in Iraq. Of 84 enteropathic viruses identified, 61 (73%) were noroviruses and these included both unknown strains and those that were common in the UK and Europe. Of the 10 viral outbreaks, 3 (30%) occurred in medical units, 5 (50%) were associated with large-scale relief in place (RiP) deployments and 5 (50%) involved >3 different viruses, which is strongly suggestive of food or water contamination. Conclusion: These findings can help to predict future viral gastroenteritis outbreaks and target improved prevention strategies appropriately. However, more systematic studies are now required.